AN ANALYSIS OF CONFLICT ZONES IN CONTEMPORARY NIGERIA: A TAPESTRY OF TENSIONS - EMMANUEL ZINGFA DANNAP; SAMUEL ALEGWU OMANCHI (International Studies Journal)
Nigeria, a nation brimming with potential, grapples with a complex tapestry of conflicts woven across its vast territory. This analysis delves into the multifaceted web of contention, dissecting the primary zones of discord that impede the nation's progress. From the insurgency fueled by Boko Haram in the North-East to the farmer-herder clashes in the North-Central, resource conflicts in the Niger Delta, and separatist agitations echoing in the South-East, we examine the actors, causes, and impacts of these conflicts. For the purpose of this paper, a qualitative method of data collection has been adopted; materials were derived from secondary sources of data. Recognizing the interconnectedness of these issues and their root causes in poverty, inequality, and governance shortcomings, we advocate for a multi-pronged approach to peacebuilding, encompassing security measures, dialogue, grievance redress, development initiatives, and social cohesion efforts. By understanding the threads binding these conflicts, we can begin to untangle the tapestry and pave the way for a more peaceful and prosperous Nigeria.